IMPROVING STUDENTS’ WRITING SKILL IN NARRATIVE TEXT BY USING PIE (POINT, ILLUSTRATION,EXPLANATION) STRATEGY AT SMPN 8 MAKASSAR - Nopianti, Nopianti; Rampeng, Rampeng; Muliati, Muliati (Lembaga Jurnal FKIP Universitas Bosowa, 2024)
The purpose of this research was to improve students’ writing skill by using Pie (Point, Illustration, Explanation) Strategy in narrative text for eight grade Students’ of SMPN 8 Makassar in the Academic year 2022/2023. The research used the pre-experiment with pre-test and post-test research.The total population of the research was the eight grade Students of which consist of 36 Students. Than, the data had been collecting by using writing test which was applied in pre-test and post-test. The process of the research was applied four times. The research was conducted by giving treatment and succeeded in improving Students’ writing skill in several aspect, namely content, organization, vocabulary, grammar, and mechanic.The treatment was carried out using PIE Strategy in narrative text. After conducting the research then the data were analyzed using test analysis on SPSS 16. The result of the average writing skill score on pre-test and post- test was 47.61. After the reserarcher gave treatment using Pie Strategy, it turned out that the score of student writing skill in narrative text in the post-test increased to 79.03 . Therefore, the researcher concludes that writing skill in narrative text using PIE strategy can improve the writing narrative text ability of class VIII.9 Students’ at SMPN 8 Makassar.Keywords: Writing, skill, Narrative,text, PIE (Point, Illustration, Explanation)